Penerapan Konsep Continuous Review (Q,r) Pada Model Economic Order Quantity (EOQ) Uutuk Mengoptimalkan Persediaan Bahan Baku Minuman - Adi Wahyu Romariardi; Mustafid Mustafid; Suryono Suryono (JSINBIS (Jurnal Sistem Informasi Bisnis), 2022)
The challenge in controlling the supply of beverage ingredients is strongly influenced by the stable condition of supply, prices and differences in the shelf life of the beverage ingredients themselves. The high cost of beverage ingredients such as milk, flavoring powder and the difficulty of finding supplies of certain beverage ingredients, all of the increase in prices and difficulties will certainly affect operations. There are three choices, either increase the price, reduce the profit, or reduce the portion size. All these choices will not be easy to decide. This study aims to build an information system by applying the concept of continuous review (Q,r) on the economic order quantity (EOQ) model to optimize the supply of beverage ingredients. With the application of the concept of continuous review (Q, r) in the economic order quantity (EOQ) model on robusta coffee beans  produces  the order quantity is 521.15 grams each time an order is at the inventory level at 746 grams, palm sugar produces the order quantity is 1,430.71 grams every time you order at a stock level at 1124 grams, UHT milk produces the order quantity is 1,188.4 ml each time you order at a stock level at 7462 ml, and sweetened condensed milk produces an order amount of 802,6 grams each time you order at a stock level of 758 grams.